KAJIAN KONSEP KENYAMANAN JALUR PEDESTRIAN DI JL. STASIUN KERETA API MEDAN DAN JL. PALANG MERAH MEDAN - Mastoni, Eli; Simamora, Nicolaus; -, Yulianto (Unika Santo Thomas, 2018)
Pedestrian paths are very important in urban design elements, especially trade areas. Similarly on Jl. Medan Railway Station and Jl. Medan Red Cross, but this need is not comparable to the conditions of the pedestrian path on both roads which have been damaged and not maintained, causing inconvenience. Because of this, the researchers tried to find the concept of the pedestrian path to the two roads. The research method used is a qualitative descriptive method. Then the method is analyzed based on theoretical and empirical analysis. Through the theoretical analysis and empirical analysis found several results in accordance with the hypothesis of the researcher. The results of the analysis are then made anappropriate concept on Jl. Medan Railway Station and Jl. Medan Red Cross.